EMERGENCY BURNING OF SOLID ROCKET PROPELLANT: DAMAGE RISK ASSESSMENT TO PEOPLE IN THE WORKPLACE - Biliaiev, M. M.; Berlov, O. V.; Biliaieva, V. V.; Kozachyna, V. A.; Kalashnikov, I. V. (Science and Transport Progress, 2020)
Purpose. This work includes the development of a computer model to calculate the risk of thermal damage to people in the shop in case of emergency burning of solid rocket propellant. Methodology. To calculate the temperature field in the shop in order to determine the zones of thermal damage to workers in the building, the equation expressing the law of energy conservation was used. Based on this modeling equation, the temperature field in the shop is calculated in the presence of a source of heat emission – burning solid rocket propellant. To calculate the velocity field of air flow in the shop, taking into account the location of obstacles in the path of heat wave propagation, we used the model of vortex-free air motion – the equation of the velocity potential. A two-step finite difference scheme of conditional approximation is used to numerically solve the equation for the velocity potential. A difference splitting scheme was used to numerically solve the energy equation. At the first stage of construction of the difference splitting scheme of the two-dimensional energy equation into the system of one-dimensional equations is performed. Each one-dimensional equation allows you to calculate the temperature change in one coordinate direction. The point-to-point computation scheme is used to determine the temperature. When conducting a computational experiment, the air exchange in the building is taken into account. The risk assessment of thermal damage to personnel in the building is performed for different probabilities of the place of emergency combustion of solid rocket propellant. Findings. Using numerical model prediction of the potential risk areas of thermal damage to staff in the shop for a variety of emergency situations was performed. Originality. A computer model for rapid assessment of the potential risk of damage to people in the shop in case of emergency burning of solid rocket propellant was constructed. Practical value. The authors developed a code that allows you to quickly simulate the temperature fields formation in the shop in case of emergency burning of solid rocket propellant and to identify potential areas of thermal damages to workers based on this information. The developed computer program can be used to assess the risk of thermal damage in the chemical industry in case of emergency.